2010
DOI: 10.1051/0004-6361/200912548
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between technetium and lithium in a sample of oxygen-rich AGB variables

Abstract: Context. The elements technetium and lithium are two important indicators of internal nucleosynthesis and mixing in late-type stars. Studying their occurrence and abundance can give deep insight into the structure and evolution in the late phases of the stellar life cycle. Aims. The aims of this paper are: 1) to revisit the Tc content of a sample of oxygen-rich (M-type) asymptotic giant branch (AGB) variables and 2) to increase the number of such stars for which the Li abundance has been measured to provide co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 62 publications
0
30
0
Order By: Relevance
“…2 of Vanture et al (2007) to that in the super-Li rich S star V441 Cyg as shown in Fig. 7 of Uttenthaler & Lebzelter (2010) suggests that S Cas may also be a super-Li S star. The Li abundance of V441 Cyg (log (Li) = 4.4; Uttenthaler & Lebzelter 2010) as well as that of T Sgr (log (Li) = 4.2; Abia et al 1991), on the abundance scale of log (H) = 12.0, are in agreement with the predictions of HBB.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…2 of Vanture et al (2007) to that in the super-Li rich S star V441 Cyg as shown in Fig. 7 of Uttenthaler & Lebzelter (2010) suggests that S Cas may also be a super-Li S star. The Li abundance of V441 Cyg (log (Li) = 4.4; Uttenthaler & Lebzelter 2010) as well as that of T Sgr (log (Li) = 4.2; Abia et al 1991), on the abundance scale of log (H) = 12.0, are in agreement with the predictions of HBB.…”
Section: Discussionmentioning
confidence: 78%
“…However, it should be noted that predicting the M bol of Galactic S stars is not an exact science. For example, Uttenthaler & Lebzelter (2010) give M bol for V441 Cyg of −5.7, while using Eq. (1) There are other super-Li rich stars, notably WZ Cas, that present difficulties for HBB theory.…”
Section: Discussionmentioning
confidence: 99%
“…The meaning of the columns is as follows: (1) name listed in Simbad; (2) period change type; (3) range of spectral type; (4) heliocentric radial velocity; (5) presence of Tc, this paper; (6) presence of Tc, previous studies; (7) effective temperature; (8) abundance of Li; (9) rate of period change; (10) period as given in Templeton et al (2005); (11) period found in this study; (12) mean J − K colour; (13) absolute K magnitude; (14) bolometric magnitude. References of previous studies on Tc content: (1) Little-Marenin & Little (1979); (2) Little et al (1987); (3) Vanture et al (1991); (4) Merrill (1952); (5) Uttenthaler & Lebzelter (2010); (6) Lebzelter & Hron (1999). Abbreviations mean: "prob" = probably, "dbfl" = doubtful.…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…The surprise in this list is R Hya, which was previously classified by Uttenthaler & Lebzelter (2010) as Tc-poor on the basis of a UVES spectrum of that star. After careful inspection of all Tc lines in the observed range and a comparison between the UVES and the Hermes spectrum of R Hya, it became clear that this star does indeed have Tc in its atmosphere, in contrast to the findings of Uttenthaler & Lebzelter (2010). The UVES observations on 6 July 2000 were performed near maximum light of R Hya, while the Hermes observations were done about half-way between a maximum and a minimum.…”
Section: Technetium Contentmentioning
confidence: 99%
“…In addition, thermohaline mixing driven by 3 He-burning has been proposed to be the most likely process modifying the photospheric compositions of bright low-mass red giant stars (Charbonnel & Zahn 2007b; for references on the abundance anomalies at that evolution Results tables are only available at the CDS via anonymous ftp to cdsarc.u-strasbg.fr (130.79.128.5) or via http://cdsarc.u-strasbg.fr/viz-bin/qcat?J/A+A/543/A108 phase, see Charbonnel & Lagarde 2010, hereafter Paper I;and Lagarde et al 2011, hereafter Paper II). During the thermalpulse phase on the asymptotic giant branch (TP-AGB), thermohaline mixing was found to lead to lithium production (Paper I; Stancliffe 2010), accounting for the Li abundances observed in oxygen-rich AGB variables of the Galactic disk (Uttenthaler & Lebzelter 2010). In summary and as discussed in Papers I and II of this series (see also Charbonnel & Zahn 2007b), the effects of both rotation-induced mixing and thermohaline instability as described presently do account very nicely for most of the spectroscopic observations of low-and intermediate-mass stars at various metallicities.…”
Section: Introductionmentioning
confidence: 99%